Strategies for Treating Alzheimer’s: Current Approaches and Future Perspectives - Adriana Skuba; Katarzyna Załuska; Agnieszka Świdniak; Marta Biskup; Aleksandra Bartoszek; Karolina Kopeć; Agnieszka Marut; Jagoda Misiuk; Julia Adamiuk; Sylwia Nykiel (Quality in Sport)
Introduction and Purpose: